2006
DOI: 10.17221/5578-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens in suckling piglets with diarrhoea and its PCR typing and prevalence in the Czech Republic in 2001-2003

Abstract: Out of the total of 153 farms under investigation that had been experiencing diarrhoea in suckling piglets, the presence of Clostridium perfringens was detected on 60 farms (39.2%). PCR typing of isolates prepared by anaerobic cultivation was carried out by multiplex PCR. C. perfringens type A (37.9%) and type C (1.3%) were detected on 58 and 2 farms, respectively. The cpb2 gene was found in 79.3% strains of C. perfringens type A and in 100% strains of type C. An evaluation of the prevalence of positive identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The β2-toxin is being associated mainly with type A but has also been identified in association with types C and E in piglets and calves, respectively [32]. Similar findings by other investigators have also indicated that none of the isolates studied was positive to specific sequences of the gene coding the enterotoxin production (cpe) [33,34]. The enterotoxin (cpe) plays an important role in the development of intestinal disease in many animal species including man [7,35].…”
supporting
confidence: 77%
“…The β2-toxin is being associated mainly with type A but has also been identified in association with types C and E in piglets and calves, respectively [32]. Similar findings by other investigators have also indicated that none of the isolates studied was positive to specific sequences of the gene coding the enterotoxin production (cpe) [33,34]. The enterotoxin (cpe) plays an important role in the development of intestinal disease in many animal species including man [7,35].…”
supporting
confidence: 77%
“…Attaching special attention to the development mechanism of severe course of the Perfringens disease it can be stated that it is endowed with high morbidity and mortality. According to the authors, in the pig-breeding farms of Hungary massive losses of piglets occurred due to Perfringens, which is followed by annual outbreaks for a long period (Altukhov and Dushenin, 1987;Urguev, 1987;Kudryashov, 1990;Satio, 1990;Czanderlova, et al, 2006;Salimov, 2006;Kudryashov and Svyatkovskiy, 2007;Sargsyan, 2012;Sidorchuk and Masimov, 2024). Complications of enteritis in newborn piglets can be caused by opportunistic bacteria, viruses and endoparasites belonging to the genera Escherichia coli and Salmonella.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%